Samværsdans i lærerutdanningen – et inkluderende og bevegelig sammentreff - Stig-Ivan Nygård; Solveig Fretheim (Musikk og Tradisjon)
In this article we are curious about what social dance can offer student teachers in physical education. What might form and enrich their educational journey so they can feel competent and empowered (Rustad, 2017) to teach dance? How can social dance enhance excitement and develop an appetite for teaching (Biesta, 2017), in order to move, flourish and exist as teachers? The study is placed in the generous categorization of practice-led research (Barret & Bolt, 2009), with educational experiences. Adopting a duoethnographic methodological approach (Norris & Sawyer, 2012) we investigate how social dance unfolds in the field of physical education. In addition to the teaching perspective, we base our data material on the students’ experiences with the social dance sessions, followed up in interviews of six students. We use thematic analysis (Braun & Clarke, 2006) to interpret the data material. We lean on Biesta’s (2014, 2017) educational theories, Bandura’s (1997) theory of ’self-efficacy’ and Bresler’s (2018, 2019) ideas on beginner’s mind and ways of knowing. We draw attention to the experiences of engaging, embodied and collective learning processes. Our findings support that participation in the social dance (here with a focus on linedance, reinlender, and bachata) was an enriching experience and contributed significantly to a wider perspective on physical education and embodied leadership, a sense of community and companionship in the dance space.